Composite Composite with Silicon Carbide and Method for Producing the Same - Patent application

By forming a silicon carbide composite through C-O-M or Si-O-M bonding, the silicon oxide layer is minimized, enhancing thermal and electrical conductivity between bonded substrates, addressing the conductivity decrease in existing methods.

JP7606743B2Active Publication Date: 2024-12-26NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021041360
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-15
Publication Date
2024-12-26
Estimated Expiration
2041-03-15

AI Technical Summary

Technical Problem

Existing methods for bonding silicon substrates with silicon carbide substrates result in a silicon oxide layer that decreases thermal and electrical conductivity between the bonded substrates.

Method used

A silicon carbide composite is formed through C-O-M or Si-O-M bonding by introducing OH onto the surfaces of the substrates and applying dehydration energy, reducing the oxide layer to enhance conductivity.

Benefits of technology

The method enables efficient heat and electric conduction between bonded substrates with improved thermal and electrical conductivity, and can be easily manufactured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606743000001
    Figure 0007606743000001
  • Figure 0007606743000002
    Figure 0007606743000002
  • Figure 0007606743000003
    Figure 0007606743000003
Patent Text Reader

Abstract

To provide a silicon carbide composite that is expected to have efficient thermal and electrical conduction between bonding substrates.SOLUTION: A silicon carbide composite includes a first substrate including silicon carbide having a silicon oxide layer SiOx on the surface, and a second substrate including an oxide layer MO of an element M, which is one or more of the metals that form oxides in air (excluding alkali metals and alkaline earth metals), Si, Ge, As, Se, Sb, and C in diamond on the surface, and is bonded to the first substrate such that the MOy side faces the SiOx side, the second substrate is bonded to the first substrate by C-O-M bonding of at least a portion of C in silicon carbide and / or Si-O-M bonding of at least a portion of Si in silicon carbide.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present application relates to a composite in which multiple substrates, including a substrate comprising silicon carbide, are bonded together, and a method for manufacturing the same. [Background technology]

[0002] Silicon carbide substrates are used as heat dissipation or insulating substrates for semiconductor devices. Silicon carbide substrates are often bonded to other substrates, such as other silicon carbide substrates or silicon substrates. A method for bonding a silicon substrate and a silicon carbide substrate in the atmosphere at a relatively low temperature using an oxidation treatment is known (Non-Patent Document 1). In this method, the surface oxide layers of the silicon substrate and the silicon carbide substrate are OH-modified by an oxidation treatment such as oxygen plasma treatment, and the OH-modified surfaces are then placed together and heated to about 200°C to cause a dehydration reaction, thereby bonding the silicon substrate and the silicon carbide substrate.

[0003] This method allows a silicon substrate and a silicon carbide substrate to be bonded in air without applying a special bonding load. Furthermore, because the bonding temperature is relatively low at around 200°C, it is possible to directly bond a silicon carbide substrate to a heterogeneous substrate with a thermal expansion coefficient close to that of silicon carbide. However, a silicon oxide layer with a thickness of approximately 4 to 9 nm exists at the bonding interface of the silicon-silicon carbide bonded substrate obtained by this method. This silicon oxide layer reduces the thermal and electrical conductivity between the bonded substrates. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] Xu, J., Wang, C., Li, D., Cheng, J., Wang, Y., Hang, C., & Tian, ​​Y., Fabrication of SiC / Si, SiC / SiO2, and SiC / glass heterostructures via VUV / O3 activated direct bonding at low temperature, Ceramics International, 2019, 45(3), p.4094-4098 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present application is to provide a composite that can be expected to provide efficient thermal and electrical conduction between joined base materials, and a method for easily producing this composite. [Means for solving the problem]

[0006] A silicon carbide composite according to one embodiment of the present application comprises a first substrate having silicon carbide on at least a portion of its upper surface, and a second substrate having, on at least a portion of its lower surface, an element M which is one or more of metal elements other than alkali metals and alkaline earth metals, Si, Ge, As, Se, Sb, C in diamond, and C in silicon carbide, and the upper surface of the first substrate and the lower surface of the second substrate are joined by COM bonding between at least a portion of the C in the silicon carbide on the upper surface of the first substrate and at least a portion of the M on the lower surface of the second substrate.

[0007] Another embodiment of the silicon carbide composite of the present application comprises a first substrate having silicon carbide on at least a portion of its upper surface, and a second substrate having, on at least a portion of its lower surface, an element M which is one or more of metal elements other than alkali metals and alkaline earth metals, Si, Ge, As, Se, Sb, C in diamond, and C in silicon carbide, wherein the upper surface of the first substrate and the lower surface of the second substrate are joined by Si-OM bonding between at least a portion of the Si in the silicon carbide on the upper surface of the first substrate and at least a portion of the M on the lower surface of the second substrate.

[0008] Another embodiment of the silicon carbide composite of the present application comprises a first substrate having silicon carbide on at least a portion of its upper surface; an intermediate layer composed of an oxide of silicon carbide and having a thickness of 2.6 nm or less; and a second substrate having, on at least a portion of its lower surface, an element M which is one or more of metal elements excluding alkali metals and alkaline earth metals, Si, Ge, As, Se, Sb, C in diamond, and C in silicon carbide, and the upper surface of the first substrate and the lower surface of the second substrate are joined via the intermediate layer.

[0009] The method for producing a silicon carbide composite of the present application comprises a hydroxylation step in which one substrate has silicon carbide on at least a portion of its upper surface with an oxide formed on the surface, undergoes a reduction treatment to reduce the oxide and introduce OH groups onto the upper surface; and a joining step in which the lower surface of the other substrate has, on at least a portion of its lower surface, a hydroxylated product M-OH of element M, which is one or more of metal elements excluding alkali metals and alkaline earth metals, Si, Ge, As, Se, Sb, C in diamond, and C in silicon carbide, brought into contact with the upper surface onto which OH groups have been introduced in the hydroxylation step, and dehydration energy is applied to this contact portion to cause a dehydration reaction, thereby joining the one substrate to the other substrate. [Effects of the Invention]

[0010] The silicon carbide composite of the present application can be expected to provide efficient thermal and electrical conduction between bonded substrates. Furthermore, the method for producing a silicon carbide composite of the present application can easily provide a silicon carbide composite that can be expected to provide efficient thermal and electrical conduction between bonded substrates. [Brief explanation of the drawings]

[0011] [Figure 1] 1 is a conceptual diagram showing the manufacturing process of a silicon carbide composite of Example 1. FIG. [Figure 2] 1 is a planar image of the silicon carbide composite obtained in Example 1. [Figure 3] FIG. 3 is a conceptual diagram showing the manufacturing process of the silicon carbide composite of Example 2. [Figure 4] 1 is a planar image of the silicon carbide composite obtained in Example 2. [Figure 5] 10 is a planar image taken from above when the center of the silicon carbide composite obtained in Example 2 is cut with a dicing saw. [Figure 6] FIG. 1 is a conceptual diagram showing the manufacturing process of a silicon carbide composite according to Example 3. [Figure 7] 1 is a planar image of the silicon carbide composite obtained in Example 3. [Figure 8] FIG. 1 is a conceptual diagram showing the manufacturing process of a silicon carbide composite according to Example 4. [Figure 9] 1 is a planar image of the silicon carbide composite obtained in Example 4. [Figure 10] 1 is a transmission electron microscope image of an interface of the silicon carbide composite obtained in Example 4. [Figure 11] 1 is an energy dispersive X-ray spectrum of the interface of the silicon carbide composite obtained in Example 4. [Figure 12] FIG. 1 is a conceptual diagram showing the manufacturing process of a silicon carbide composite of Example 5. [Figure 13] 10 is an image of the silicon carbide composite obtained in Example 5 taken from obliquely above. [Figure 14] 10 is an ultrasonic microscope image of the interface of the silicon carbide composite obtained in Example 5. DETAILED DESCRIPTION OF THE INVENTION

[0012] The silicon carbide composite of the first embodiment of the present application comprises a first substrate and a second substrate. Examples of the first substrate and the second substrate include a substrate having a thin, flat plate shape and a solid object having a shape thicker than the substrate. The first substrate comprises silicon carbide on at least a portion of its upper surface. The "upper surface" in this application does not necessarily refer to the upper surface in the vertical direction. In other words, the "upper surface" of the substrate in this application is the surface of the substrate that can be positioned on the upper side in the vertical direction as a result of appropriately rotating the substrate around any rotation axis. Therefore, the upper surface of the first substrate simply refers to the surface that is bonded to the second substrate.

[0013] The first substrate may be made of silicon carbide, or may contain a material other than silicon carbide as long as at least a portion of the upper surface is silicon carbide. Furthermore, the silicon carbide on the upper surface of the first substrate may be silicon carbide from which at least a portion of a surface oxide film, such as a native oxide film, has been removed. The silicon carbide on the upper surface of the first substrate may be single-crystal silicon carbide or polycrystalline silicon carbide. As described later in the examples, a silicon carbide composite was successfully produced even when the upper surface of the first substrate was polycrystalline silicon carbide. The use of polycrystalline silicon carbide can reduce the cost of the silicon carbide composite.

[0014] The second substrate has a predetermined element M on at least a portion of its lower surface. The "lower surface" in this application does not necessarily refer to the lower surface in the vertical direction. In other words, the "lower surface" of the substrate in this application is the surface of the substrate that can be positioned lower in the vertical direction as a result of appropriately rotating the substrate around an arbitrary rotation axis. Therefore, the lower surface of the second substrate simply refers to the surface that is bonded to the first substrate.

[0015] The predetermined element M is one or more of the metal elements excluding alkali metals and alkaline earth metals, Si, Ge, As, Se, Sb, C in diamond, and C in silicon carbide. The metal elements excluding alkali metals and alkaline earth metals are Al, Sc with atomic number 21 to Ga with atomic number 31, Y with atomic number 39 to Sn with atomic number 50, and La with atomic number 57 to Pb with atomic number 82.

[0016] The second substrate may be made of diamond, or may contain a material other than diamond as long as at least a portion of the lower surface is made of diamond. The second substrate may be made of silicon carbide, or may contain a material other than silicon carbide as long as at least a portion of the lower surface is made of silicon carbide. The silicon carbide on the lower surface of the second substrate may be silicon carbide from which at least a portion of a surface oxide film, such as a thermal oxide film or a native oxide film, has been removed.

[0017] Furthermore, the second substrate may be composed of one or more elements of metal elements other than alkali metals and alkaline earth metals, Si, Ge, As, Se, and Sb, or may be composed of compounds containing these elements. Alternatively, the second substrate may contain other substances as long as at least a portion of the lower surface is composed of these elements or compounds containing these elements. Even if the lower surface of the second substrate is composed of compounds of these elements, these elements themselves may be present in part of the lower surface. Therefore, when the lower surface of the second substrate is composed of compounds of these elements, it corresponds to a "second substrate having these elements on at least a portion of the lower surface."

[0018] Furthermore, at least a portion of a surface oxide film, such as a thermal oxide film or a natural oxide film, on the underside may be removed to form a "second substrate having these elements on at least a portion of the underside." Examples of the second substrate include a diamond substrate, a Si substrate, a SiC substrate, a SiN substrate, a Ge substrate, a GaAs substrate, a GaN substrate, an InP substrate, a Cu substrate, an Al substrate, an AlN substrate, a Ti substrate, a TiN substrate, a SiO2 substrate, a Ga2O3 substrate, an Al2O3 substrate, a CuO substrate, a ZnO substrate, a TiO2 substrate, and a Y3Al5O 12 Examples of such a substrate include a LiNbO3 substrate, a LiTaO3 substrate, and a CH3NH3PbI3 substrate.

[0019] In the silicon carbide composite of the first embodiment, the upper surface of the first substrate and the lower surface of the second substrate are bonded by COM bonding between at least a portion of the C in the silicon carbide on the upper surface of the first substrate and at least a portion of the M on the lower surface of the second substrate. Alternatively, or in addition to this, the upper surface of the first substrate and the lower surface of the second substrate may be bonded by Si-OM bonding between at least a portion of the Si in the silicon carbide on the upper surface of the first substrate and at least a portion of the M on the lower surface of the second substrate. The formation of COM bonds and Si-OM bonds can be confirmed, for example, by FT-IR.

[0020] Whether a C-M bond or an Si-O-M bond is formed depends on the crystal plane of the silicon carbide surface on the upper surface of the first substrate. For example, when the silicon carbide surface is the (000-1) plane, a C-M bond is formed, and when the silicon carbide surface is the (0001) plane, a Si-O-M bond is formed. When the silicon carbide on the upper surface of the first substrate has a polycrystalline structure, both a C-M bond and an Si-O-M bond are formed. Because the second substrate is firmly bonded to the first substrate by the C-M bond and / or the Si-O-M bond, the silicon carbide composite of the first embodiment efficiently conducts heat and electricity between the substrates.

[0021] The silicon carbide composite of the second embodiment of the present application comprises a first substrate, an intermediate layer, and a second substrate. The first substrate and second substrate of the silicon carbide composite of the second embodiment are the same as the first substrate and second substrate of the silicon carbide composite of the first embodiment, and therefore a description thereof will be omitted. The intermediate layer is composed of an oxide of silicon carbide. The oxide of silicon carbide is a substance composed of Si, C, and O and has a C-Si-O bond or a Si-C-O bond. In the silicon carbide composite of the second embodiment, the upper surface of the first substrate and the lower surface of the second substrate are bonded via the intermediate layer.

[0022] That is, the intermediate layer functions as an intervening layer that bonds the first substrate and the second substrate. The thickness of the intermediate layer is 2.6 nm or less. Because the thickness of the intermediate layer is 2.6 nm or less, the silicon carbide composite of the second embodiment has superior thermal conductivity and electrical conductivity between the substrates, compared to the silicon-silicon carbide bonded substrate of Non-Patent Document 1, in which a silicon oxide layer with a thickness of about 4 nm to 9 nm is interposed between the silicon substrate and the silicon carbide substrate.

[0023] The thickness of the native oxide film formed on the surface of silicon carbide is approximately 1.3 nm, and the thickness of the native oxide films formed on the surfaces of metal elements other than alkali metals and alkaline earth metals, Si, Ge, As, Se, and Sb, is also approximately 1.3 nm. Therefore, for example, compared to a laminate in which the surfaces of a silicon carbide substrate and a silicon substrate, on which a native oxide film is formed, are closely attached to each other, the silicon carbide composite of the second embodiment, in which the first substrate is a silicon carbide substrate, the second substrate is a silicon substrate, and the thickness of the intermediate layer is 2.6 nm or less, has the same or better thermal conductivity and electrical conductivity between the substrates.

[0024] Furthermore, compared to a laminate in which two substrates, one of which has a native oxide film formed on its surface only, such as a Ga2O3 substrate and a silicon carbide substrate with a native oxide film formed on its surface, are tightly bonded together with this native oxide film sandwiched between them, the silicon carbide composite of the second embodiment, in which the first substrate is a silicon carbide substrate, the second substrate is a Ga2O3 substrate, and the thickness of the intermediate layer is 1.3 nm or less, has the same or better thermal conductivity and electrical conductivity between the substrates.

[0025] Therefore, the thickness of the intermediate layer is preferably 1.3 nm or less. To prevent a decrease in thermal conductivity and electrical conductivity between the substrates, the thinner the intermediate layer, the better. Furthermore, in the silicon carbide composite of each embodiment, the shear strength between the first substrate and the second substrate is preferably 0.1 MPa or more so that the first substrate and the second substrate can be used without peeling. The shear strength is measured using a die shear test (JEITA ED-4703).

[0026] The method for manufacturing a silicon carbide composite according to an embodiment of the present application includes a hydroxylation step and a bonding step. In the hydroxylation step, an oxide of one of the substrates is reduced to introduce OH groups onto the upper surface. The one of the substrates has silicon carbide with the oxide formed on its surface on at least a portion of its upper surface. The oxide may be a native oxide of silicon carbide. Note that silicon carbide oxide is a substance composed of Si, C, and O and has a C-Si-O bond or a Si-C-O bond. This reduction treatment converts, for example, C-Si-O and / or Si-C-O to C-Si-OH and / or Si-C-OH, respectively. The reduction treatment can be exemplified by treatment with HF.

[0027] In the bonding step, the lower surface of the other substrate, which has a hydroxylated product M-OH of a predetermined element M on at least a portion of its lower surface, is brought into contact with the upper surface of the one substrate to which OH has been introduced in the hydroxylation step, and dehydration energy is applied to the contact area to cause a dehydration reaction, bonding the one substrate to the other substrate to obtain a silicon carbide composite. Note that the predetermined element M is one or more of metal elements excluding alkali metals and alkaline earth metals, Si, Ge, As, Se, Sb, C in diamond, and C in silicon carbide.

[0028] Examples of methods for introducing OH into M present in the other substrate to form M-OH on at least a portion of the lower surface include reduction or oxidation treatments in which the lower surface of the other substrate is treated with a mixture of NH3 and HO, a mixture of H2SO4 and HO, or HF solution, or by irradiating with oxygen plasma. In the bonding process, the lower surface of the other substrate and the upper surface of one substrate are brought into contact in the atmosphere. This allows for easy production of silicon carbide composites.

[0029] Examples of dehydration energy include thermal energy, light energy, electrical energy, and chemical energy. In this embodiment, the contact area between one substrate and the other substrate is heated to a temperature of approximately 200°C. This dehydration reaction forms COM bonds and / or Si-OM bonds, bonding the one substrate to the other. This bonded area has sufficient shear strength. [Example]

[0030] Example 1 FIG. 1 conceptually illustrates the manufacturing process of the silicon carbide composite of Example 1. A disk-shaped Si substrate (T4APX, Matsuzaki Manufacturing Co., Ltd.) (raw material for the second substrate) with a diameter of 100 mm, a thickness of 0.4 mm, and a (100) plane surface was cut into 5 mm squares. A 1 mm region from the uneven cut edge of the cut Si substrate toward the center was chemically etched away using tetramethylammonium hydroxide to a depth of approximately 100 μm. The Si substrate was immersed for 10 minutes in a room-temperature mixture of 10 mL of 28% aqueous ammonia, 10 mL of 35% aqueous hydrogen peroxide, and 50 mL of pure water. The Si substrate was then rinsed with pure water for 5 minutes. OH groups were introduced into the surface of the Si substrate, forming Si-OH groups.

[0031] Separately, a disk-shaped SiC substrate (Cree, W4NRE4C-V200) (the raw material for the first substrate) with a diameter of 75 mm, a thickness of 0.350 mm, and a (0001) surface was immersed in a room-temperature mixture of 50 mL of 49% hydrofluoric acid and 150 mL of pure water for 5 minutes. The SiC substrate was then rinsed with pure water for 5 minutes. As a result, the surface oxide film of the SiC substrate was removed, and OH groups were introduced onto the surface, forming Si-OH groups. The Si-OH side of the obtained Si substrate and the Si-OH side of the SiC substrate were brought into contact in the air and stored in a sealed container with a desiccant for 3 days. The substrate was then heated at 200°C for 5 hours to induce a dehydration reaction. A silicon carbide composite was obtained in which the SiC substrate and the Si substrate were bonded by Si-O-Si bonding.

[0032] Figure 2 is a planar image of the silicon carbide composite obtained in Example 1, observed from above, i.e., through the transparent SiC substrate. A 1 mm region from the edge of the Si substrate toward the center was chemically removed, and therefore not bonded to the SiC substrate. In contrast, no Newton's rings originating from the non-bonded portion were observed in the central 3 mm square region of the Si substrate, indicating good bonding. When a shear stress of 6.6 MPa was applied to the Si substrate on the left side of Figure 2 and a shear stress of 5.1 MPa was applied to the Si substrate on the right side of Figure 2, both substrates peeled off from within the Si substrate and from the bonded interface with the SiC substrate. In this way, a silicon carbide composite was obtained in which the shear strength between the first substrate and the second substrate was 5 MPa or more.

[0033] Example 2 FIG. 3 conceptually illustrates the manufacturing process of the silicon carbide composite of Example 2. A circular SiC substrate (manufactured by II-Six Corporation) with a diameter of 100 mm, a thickness of 0.350 mm, and a (000-1) plane surface (the raw material for the first and second substrates) was cut into a rectangular plate measuring 10 mm long and 11 mm wide. The SiC substrate was immersed in a room-temperature mixture of 50 mL of 49% hydrofluoric acid and 150 mL of pure water for 5 minutes. The SiC substrate was then rinsed with pure water for 5 minutes. As a result, the oxide film on the surface of the SiC substrate was removed, and OH groups were introduced to the surface, forming C—OH groups. The C—OH-side surfaces of the two resulting SiC substrates were brought into contact with each other in the air and stored in a sealed container with a desiccant for 3 days. The substrates were then heated at 200°C for 5 hours to induce a dehydration reaction. A silicon carbide composite was obtained in which the SiC substrates were bonded together by C—O—C bonding, i.e., two SiC substrates were bonded together.

[0034] Figure 4 is a planar image taken from above of the silicon carbide composite obtained in Example 2. As shown in Figure 4, the upper right corner of the upper SiC substrate of the silicon carbide composite of Example 2 is missing, and the area immediately below and to the left of this missing portion is bright. This is thought to be because the two SiC substrates could not be bonded due to unevenness caused by cutting the SiC substrate. In contrast, the center of the silicon carbide composite was relatively dark. It is thought that the two SiC substrates are bonded in the center of the silicon carbide composite. Figure 5 shows a planar image taken from above of the silicon carbide composite after cutting the center with a dicing saw. As shown in Figure 5, the two SiC substrates of the silicon carbide composite did not peel off even after the cutting process.

[0035] Example 3 Figure 6 conceptually illustrates the manufacturing process for the silicon carbide composite of Example 3. The surface of a rectangular, plate-shaped single-crystal β-GaO substrate (Novel Crystal, T010FE2525) (the raw material for the second substrate) measuring 23 mm in length, 25 mm in width, and 0.4 mm in thickness was treated with high-purity oxygen plasma at a pressure of 60 Pa and an output of 200 W for 1 minute. As a result, a β-GaO substrate with Ga-OH formed on its surface was obtained.

[0036] On the other hand, SiC substrates with C-OH formed on the surface were fabricated in the same manner as in Example 2, except that they were cut into rectangular plates measuring 28 mm in length and 30 mm in width. The Ga-OH side surface of the obtained β-Ga2O3 substrate and the C-OH side surface of the SiC substrate were brought into contact in the air and stored in a sealed container with a desiccant for 3 days. The substrates were then heated at 200°C for 12 hours to induce a dehydration reaction. A silicon carbide composite was obtained in which the SiC substrate and β-Ga2O3 substrate were bonded by CO-Ga bonding.

[0037] Figure 7 is a planar image of the silicon carbide composite obtained in Example 3, observed from above, i.e., through the transparent β-Ga2O3 substrate. As shown in Figure 7, the observed Newton's rings indicate that the β-Ga2O3 substrate and the SiC substrate were not bonded in a region extending approximately 2 mm from the edge of the β-Ga2O3 substrate toward the center. This is thought to be because the surface of the β-Ga2O3 substrate in this region was convex, preventing adhesion to the SiC substrate. Furthermore, bonding was not possible in the lower center of the β-Ga2O3 substrate due to a foreign object trapped between the β-Ga2O3 substrate and the SiC substrate. On the other hand, in the region where Newton's rings were not observed, the β-Ga2O3 substrate and the SiC substrate were bonded.

[0038] Example 4 Figure 8 conceptually illustrates the manufacturing process for the silicon carbide composite of Example 4. A rectangular β-Ga2O3 thin plate (the raw material for the second substrate) measuring 20 mm in length, 15 mm in width, and 1 mm in thickness was prepared by cleavage from a single-crystal β-Ga2O3 substrate (Novel Crystal, NvD-1906-029) and the surface was treated with high-purity oxygen plasma at a pressure of 60 Pa and an output of 200 W for 1 minute. As a result, a β-Ga2O3 thin plate with Ga-OH formed on the surface was obtained.

[0039] On the other hand, a SiC substrate with C-OH formed on its surface was fabricated in the same manner as in Example 3. The Ga-OH side of the β-Ga2O3 thin plate obtained above was brought into contact with the C-OH side of the SiC substrate in the air and stored in a sealed container with a desiccant for 3 days. The resulting mixture was then heated at 250°C for 24 hours to induce a dehydration reaction. A silicon carbide composite was obtained in which the SiC substrate and β-Ga2O3 thin plate were bonded together by CO-Ga bonding.

[0040] Figure 9 shows a planar image of the silicon carbide composite obtained in Example 4, taken from above, i.e., through the transparent β-Ga2O3 thin plate, observing the SiC substrate. In areas where the β-Ga2O3 thin plate and SiC substrate could not be bonded, white bubbles were observed at the interface between the β-Ga2O3 thin plate and the SiC substrate. These white bubbles are thought to be due to surface contamination or crystal cleavage of the β-Ga2O3 thin plate. On the other hand, in areas where no bubbles were observed, the β-Ga2O3 thin plate and SiC substrate were bonded.

[0041] FIG. 10 shows a transmission electron microscope image of the interface of the silicon carbide composite obtained in Example 4. An intermediate layer of approximately 0.6 nm was observed at the bonding interface between the β-Ga2O3 thin plate and the SiC substrate. In the silicon-silicon carbide bonded substrate described in Non-Patent Document 1, an amorphous layer of approximately 4 nm to 9 nm thick composed of S, O, and C was observed between the silicon substrate and the silicon carbide substrate, whose surfaces had been oxidized. However, as in this example, by reducing the oxide formed on the silicon carbide surface, the thickness of the intermediate layer at the bonding interface of the substrates could be reduced to approximately 0.6 nm to 1.3 nm, the thickness of the surface oxide film of the silicon carbide. Therefore, the silicon carbide composite of the present application is expected to provide effective thermal and electrical conduction through the bonding interface.

[0042] It is believed that the thickness of the intermediate layer at the bonding interface of the substrates can be reduced to 0.3 nm, which is the bond length of Si-OM bonds such as Si-O-Si and Si-OC. Figure 11 shows the energy dispersive X-ray spectroscopy spectrum of the interface of the silicon carbide composite obtained in Example 4. Ga and O derived from the β-Ga2O3 thin plate, and Si and C derived from the SiC substrate, were primarily detected at the bonding interface of this silicon carbide composite. Trace amounts of Cl were also detected. This is believed to be due to contamination of the surface of the silicon carbide composite.

[0043] Example 5 FIG. 12 conceptually illustrates the manufacturing process of the silicon carbide composite of Example 5. The surface of the disk-shaped Si substrate (raw material for the second substrate) used in Example 1 was treated with high-purity oxygen plasma at a pressure of 60 Pa and an output of 200 W for 1 minute. As a result, a Si substrate with Si—OH groups formed on its surface was obtained. Meanwhile, a disk-shaped polycrystalline SiC substrate (manufactured by Tokai Fine Carbon Co., Ltd.) (raw material for the first substrate) with a diameter of 100 mm and a thickness of 0.7 mm was immersed for 5 minutes in a room-temperature mixture of 50 mL of 49% hydrofluoric acid and 150 mL of pure water. The polycrystalline SiC substrate was then rinsed with pure water for 5 minutes. As a result, OH groups were introduced into the surface of the polycrystalline SiC substrate, forming C—OH and Si—OH groups.

[0044] The Si-OH side surface of the Si substrate obtained above and the C-OH and Si-OH side surfaces of the polycrystalline SiC substrate were brought into contact in the air and stored in a sealed container with a desiccant for 3 days. The mixture was then heated at 200°C for 5 hours to cause a dehydration reaction. A silicon carbide composite was obtained in which the polycrystalline SiC substrate and the Si substrate were bonded together through CO-Si and Si-O-Si bonding. Figure 13 is an image of the silicon carbide composite obtained in Example 5 taken from an obliquely upward angle. As shown in Figure 13, it was confirmed that the polycrystalline SiC substrate and the Si substrate were bonded together in this silicon carbide composite. Figure 14 is an ultrasonic microscope image of the silicon carbide composite obtained in Example 5. The unbonded portions appear bright. As shown in Figure 14, although some portions of this silicon carbide composite were not bonded due to surface deposits, it was confirmed that approximately 95% of the composite was bonded.

Claims

1. A first substrate having silicon carbide on at least a portion of an upper surface thereof; an intermediate layer made of an oxide of silicon carbide and having a thickness of 2.6 nm or less; A second substrate having an element M on at least a portion of a lower surface thereof, the element M being one or more of metal elements other than alkali metals and alkaline earth metals, Si, Ge, As, Se, Sb, C in diamond, and C in silicon carbide; having A silicon carbide composite in which the upper surface of the first substrate and the lower surface of the second substrate are bonded via the intermediate layer.

2. In claim 1, A silicon carbide composite having an intermediate layer having a thickness of 1.3 nm or less.

3. In claim 1 or 2, A silicon carbide composite, wherein the intermediate layer has a thickness of 0.6 nm or more.

4. In any one of claims 1 to 3, A silicon carbide composite, wherein the silicon carbide on the top surface of the first substrate is polycrystalline silicon carbide.

5. In any one of claims 1 to 4, A silicon carbide composite, wherein the shear strength between the first substrate and the second substrate is 0.1 MPa or more.

6. a hydroxylation step of reducing the oxide of one of the substrates, which has silicon carbide on at least a portion of its upper surface, with HF to introduce OH onto the upper surface; a bonding process in which a lower surface of another substrate has, on at least a part of the lower surface thereof, a hydroxylated product M-OH of an element M, which is one or more of metal elements excluding alkali metals and alkaline earth metals, Si, Ge, As, Se, Sb, C in diamond, and C in silicon carbide, in contact with the upper surface to which OH has been introduced in the hydroxylation process, and a dehydration energy is applied to the contact portion to cause a dehydration reaction, thereby bonding the one substrate to the other substrate; A method for producing a silicon carbide composite having the following structure:

Citation Information

Patent Citations

  • METHOD FOR MANUFACTURING SINGLE CRYSTAL SiC SUBSTRATE

    JP2006206377A

  • Manufacturing method of silicon carbide substrate

    JP2009117533A

  • Composite substrate manufacturing method and composite substrate

    JP2014003105A

  • Composite substrate manufacturing method and composite substrate

    JP2014209527A

  • Composite body comprising diamond crystal body

    WO2020230520A1